2013
DOI: 10.3390/ijms140713979
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling in Prostate Cancer and Its Therapeutic Implication

Abstract: Activation of Hedgehog (Hh) signaling is implicated in the development and progression of several tumor types, including prostate cancer, which is still the most common non-skin malignancy and the third leading cause of cancer-related mortality in men in industrialized countries worldwide. Several studies have indicated that the Hh pathway plays a crucial role in the development as well as in the progression of this disease to more aggressive and even therapy-resistant disease states. Moreover, preclinical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 148 publications
(204 reference statements)
4
91
0
1
Order By: Relevance
“…Canonical HH pathway activation appears to be more marked in late-stage prostate cancer (22,23). In addition, results of the present study and previous studies observed a potential association between HH signaling component expression and androgen-independent prostate cancer cells (1,15). Long-term androgen deprivation may induce an upregulation of HH signaling in human specimens and in cell lines.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Canonical HH pathway activation appears to be more marked in late-stage prostate cancer (22,23). In addition, results of the present study and previous studies observed a potential association between HH signaling component expression and androgen-independent prostate cancer cells (1,15). Long-term androgen deprivation may induce an upregulation of HH signaling in human specimens and in cell lines.…”
Section: Discussionsupporting
confidence: 64%
“…Prostate cancer is the second most common malignancy in males worldwide, characterized by its high mortality and poor prognosis (1). In spite of early detection techniques and multidisciplinary therapeutic approaches, the overall 5-year survival rate remains <30% in China (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, it plays a crucial role in regulating CSCs in various human cancers including PCa by regulating target genes involved in proliferation, survival, metastasis, and auto-regulation [37,[63][64][65] . Furthermore, the Hh pathway promotes multidrug resistance by increasing the transcription of the ABC transporter proteins ABCB1 and ABCG2 in PCa [63,64] . Thus, the inhibition of the Hh signaling pathway may result in the depletion of CSCs [37,63] .…”
Section: Hh Pathwaymentioning
confidence: 99%
“…NICD and CSL form a ternary complex together with Mastermind (Mam) that recruits transcription factors activating target gene expression. Because hedgehog (Hh) signaling regulates progenitor cell fate in normal development and homeostasis, aberrant pathway activation might be involved in the maintenance of such a population in cancer [61]. Abnormal Hh signaling has been associated with diverse human malignancies including basal cell carcinoma, medulloblastoma, pancreatic and lung cancer.…”
Section: Signal For Self-renewal and Differentiation Of Stem Cellsmentioning
confidence: 99%